Modelling the oxygen uptake off-kinetics in swimming - Monteiro, A. S.; Azevedo, R.; Zacca, R.; Buzzachera, C. F.; Vilas-Boas, J. P.; Fernandes, R. J. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Analysing oxygen uptake (V.O2) kinetics during exercise is of great importance to better understand the physiological determinants of performance. A validated, free and open-source software (VO2FITTING) was recently developed to characterize V.O2 kinetics during continuous exercise (Zacca et al., 2019). The aim of the current study was to present an update of VO2FITTING, demonstrating its benefits for the analysis of post-exercise data and interpretation of V.O2 off-kinetics. METHODS The VO2FITTING was updated to allow editing, processing, filtering and modelling the post-exercise V.O2. Using mono- or bi-exponential models, it characterizes the V.O2 response at different exercise intensity domains, with installation instructions and supplementary documents available at https://shiny.cespu.pt/vo2_news/. In swimming, this software is useful for analysing sets like 200 m incremental intermittent protocol (see Monteiro et al., 2020), with V.O2 assessment being made breath-by-breath through a respiratory snorkel and valve system connected to a portable gas analyser unit (AquaTrainerR and K4b2, Cosmed, Italy). RESULTS Figure 1. Mono-exponential V.O2 off-kinetics model after a moderate intensity front crawl. DISCUSSION VO2FITTING allows to dynamically improve raw signals and to easily understand the model that best fits the swimming data through the software outputs (Zacca et al., 2019). The analysis of V.O2 off-kinetics allows a better understanding of the recovery phase, particularly the symmetry/asymmetry with the V.O2 on-kinetics and the post-swim physiological mechanisms.